THE RELATIONSHIP BETWEEN MASS-TRANSPORT TO CHANNEL AND ROTATING-DISK ELECTRODES - Unwin, P; Compton, R (1988)
A simple equation is presented which relates the diffusion layer thickness at a rotating disk electrode to the average diffusion layer thickness at a channel (or tubular) electrode, under the assumption that the hydrodynamic flow in both cases is laminar. It is demonstrated that, through the equation, the parameters characterising various possible electrode reaction mechanisms (ECE, DISP1, EC', CE,⋯) under transport-limited conditions at one of the two electrodes, are readily deduced once the corresponding mass transport problem has been rigorously solved at the other electrode. In addition, the relationship is shown to be equally successful when considering the chronoamperometric response at the two electrodes to a potential step, from a region in which no current flows to one corresponding, under steady-state conditions, to the passage of the transport-limited current, and also for the description of the general form of the current-potential curves for the two electrode geometries. The circumstances under which the transformation may be applied are critically assessed. © 1988.